Acute effects of cigarette smoke on inflammation and oxidative stress: a review. Issue 8 (28th July 2004) - van der Vaart, H; Postma, D S; Timens, W; Ten Hacken, N H T
Abstract : Compared with the effects of chronic smoke exposure on lung function and airway inflammation, there are few data on the acute effects of smoking. A review of the literature identified 123 studies investigating the acute effects of cigarette smoking on inflammation and oxidative stress in human, animal, and in vitro models. An acute smoking model is a relatively easy and sensitive method of investigating the specific effects of cigarette smoke on oxidative stress and inflammation. Acute smoke exposure can result in tissue damage, as suggested by increased products of lipid peroxidation and degradation products of extracellular matrix proteins. Acute cigarette smoke has a suppressive effect on the number of eosinophils and several inflammatory cytokines, possibly due to the anti-inflammatory effect of carbon monoxide. An acute smoking model can supplement other ways of studying the effects of smoking and is an as yet underinvestigated method for intervention studies in smoking related diseases.